Developing rural tourism in minority ethnic villages: Zlot and Xiaocang She Ethnic Township - Blažević, Marko; Peters, Katarina; Chen, Guisong (Hotel and Tourism Management, 2018)
This paper deals with deploring two villages, one in Europe in the eastern part of Serbia called Zlot village and one in China in Fujian province by the name of Xiaocang She Ethnic Township. These two villages have a significant population of national minorities, so their historical backgrounds and local traditions are explained in order to point to their potential of development as rural tourist destinations. Using the empowerment model, the villages can develop and reach their full potential. Provide their residents with better income and incentive to keep and share invaluable minority traditions that have been alive for a long period of time. The empowerment model can help locals improve their economic status by being involved in tourism in their respective villages. Due to the rich local traditions of the minorities living there and beautiful natural scenery, tourism potential is vast. Langde Mode should be implemented in a way of community guidance in order to improve both, rural tourism in these areas, as well as the lives of the local community.